Biaxially textured (Bi, Pb)2Sr2Ca2Cu3Ox thin films on LaAlO3 substrates fabricated via the chemical solution deposition method. (25th February 2019) - Qu, Timing; Lin, Guan; Feng, Feng; Deng, Shutong; Song, Xiuhua
Abstract: In this study, biaxially textured (Bi, Pb)2 Sr2 Ca2 Cu3 O x ((Bi, Pb)-2223) thin films were fabricated epitaxially on LaAlO3 (LAO) single crystal substrates via the chemical solution deposition (CSD) method. In order to prevent the evaporation of Bi and Pb, a sealed face-to-face architecture for sintering was utilized. According to the results of x-ray diffraction measurements including θ /2 θ -scan, ω -scan, and ϕ -scan patterns, the optimal sintering temperature was found to be 840 °C. The volume fraction of the (Bi, Pb)-2223 phase of the optimal sample was enhanced to above 80%. Favorable out-of-plane and in-plane textures were also detected, which could be attributed to an epitaxy system of (Bi, Pb)-2223 thin film and an LAO substrate with a 45° rotated alignment. A dense microstructure and thickness of about 100 nm were found by scanning electron microscopy observations of the surface morphology and cross section. The critical temperature of the optimal sample determined with the four-probe method was 103.2 K, and its critical current density values were 0.06 MA cm −2 (77 K, self-field) and 1.91 MA cm −2 (4.2 K, self-field), which were obtained by AC susceptibility measurement and a superconducting quantum interference device, respectively. This study demonstrated the feasibility of fabricating (Bi, Pb)-2223 thin films with superconducting performance via the low-cost CSD method.